Evolution of TKA design - Dall'Oca, Carlo; Ricci, M.; Vecchini, E.; Giannini, N.; Lamberti, D.; Tromponi, C.; Magnan, B. (Acta Biomedica Atenei Parmensis, 2017)
The use of Total Knee Arthroplasty (TKA) in treatment of chronic degenerative pathologies of the knee boasts of an experience of 50 years. During this period the collaboration between surgeons and engineers produced many developments in the design of the prosthesis. Today this procedure is safe and established even if in continuous development. The progress in technologies and the use of new materials let researches try again old-fashioned techniques from the past in order to be improved. This enthusiasm for those discovers is not always going hand to hand with scientific validation: many open questions remains Every different concept of the design tries to answer to special needs as the reach of the highest ROM, the reduction of pain and debris, articular geometry, the type of fixation, the modularity of augments and stems, the types of constraints, knee kinematic and of course costs.